ANALISIS TINGKAT KERENTANAN GERAKAN TANAH MENGGUNAKAN MODIFIKASI METODE STORIE STUDI KASUS DAERAH PUNDUNGSARI, KECAMATAN SEMIN, KABUPATEN GUNUNG KIDUL, DAERAH ISTIMEWA YOGYAKARTA. - Yudha Pratama, Rajawali; Rizqi, Al Hussein Flowers (ReTII, 2022)
Semin District is located in the eastern part of the Gunung Kidul mountains, precisely on the eastern slope of Gunung Kidul. This area slopes up to the foot of Mount Stage, is located on a fairly steep slope area making this area has a large potential for landslides, especially during the rainy season. In the past few years, from 2016-2020, the Gunung Kidul BMKG station in this area also often occurs landslides during the rainy season. The purpose of this paper is to map ground motion using the STORIE method. The purpose of writing the final report of this seminar are: To create a landslide susceptibility zoning map in Sirau Village using the STORIE method on a scale of 1:25,000. The research area is included in the "Wonosari Plateau" zone. Southern Mountain Zone of Java. The ground motion zoning mapping was carried out based on the STORIE method using the weighted values ​​of four parameters. The parameters used are slope, lithology, land use and rainfall. The results of STORIE processing using ArcGIS software produce a landslide susceptibility zoning map which is divided into 4 classes (very low, low, medium, high). Based on the results of ground motion mapping using the STORIE method, the most vulnerable area is Pundungsari Village which is composed of Tuff lithology from the Semilir Formation, Andesite Breccia from the Mandalika Formation, and Limestone from the Wungkal Gamping Formation.\ Keyword : Semin, Gunungkidul, STORIE, mass movement